RE-CONCEPTUALIZING COMMUNICATIVE LANGUAGE TEACHING THROUGH SOCIO-CULTURAL PERSPECTIVE - Lina Farsia (Englisia: Journal of Language, Education, and Humanities, 2016)
Communicative Language Teaching (CLT) has been know as one of the most successful approaches in teaching English to speaker of other languages. With this approach students are required to engage in communication trough interaction using the target language as much as possible. In the countries where English is taught as a foreign language or as a second language, this approach has become an ideal example on how activities are reconstructed in teaching learning activity to improve students’ ability in communicating in English both in spoken and written ways. Despites all of the advantages of CLT, there are still some the flaws found in he implementation of CLT in teaching learning activities. Therefore, in this paper, the writer will not only provide some critiques that are normally found in CLT but also suggesting some alternatives based on the socio cultural concepts to mitigate the shortcoming. The provided alternatives are aimed to re -conceptualize the CLT in based on the socio cultural perspective.